2021
DOI: 10.1049/cim2.12029
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Progress of zinc oxide‐based nanocomposites in the textile industry

Abstract: Textile materials have been enriched in function at the composite level with continuous developments in the textile industry. Zinc oxide (ZnO) nanoparticles (ZnO-NPs) are strongly influenced by ultraviolet (UV) filter, antifungal, high catalysis, and semiconductor/piezoelectric coupling characteristics. Therefore, the antibacterial property and UV resistance of ZnO-NP materials are zcomprehensively analysed to provide a basis for applying ZnO-NP in the textile industry. In addition, the textile preparation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
232
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 250 publications
(233 citation statements)
references
References 40 publications
1
232
0
Order By: Relevance
“…The better the arterial elasticity, the closer the AASI is to 0 [ 12 ]. The pulse pressure mainly depends on the ejection rate of the left ventricle, the stroke volume of the heart, and factors such as the compliance of the large arteries and the pressure reflection waves of the peripheral blood vessels, and as the pulse pressure increases, its damage to blood vessels is also strengthened; the tube wall is in a state of high tension for a long time; it is easy to fatigue and break, and the factor that regulates the vasoconstriction and relaxation function is out of proportion, and vascular endothelial dysfunction strengthens the progression of vascular sclerosis; therefore, pulse pressure has a certain role in reflecting the degree of arteriosclerosis [ 13 ]. As obtained from this experiment, according to the AASI grouping, as the AASI level increases, 24 h PP is gradually increasing, but the stability of PP is weaker than that of AASI and is susceptible to changes in blood pressure fluctuations and other factors and affects the accuracy of prediction, so the AASI in this study has become the most suitable indicator for predicting arteriosclerosis [ 14 ].…”
Section: Results and Analysismentioning
confidence: 99%
“…The better the arterial elasticity, the closer the AASI is to 0 [ 12 ]. The pulse pressure mainly depends on the ejection rate of the left ventricle, the stroke volume of the heart, and factors such as the compliance of the large arteries and the pressure reflection waves of the peripheral blood vessels, and as the pulse pressure increases, its damage to blood vessels is also strengthened; the tube wall is in a state of high tension for a long time; it is easy to fatigue and break, and the factor that regulates the vasoconstriction and relaxation function is out of proportion, and vascular endothelial dysfunction strengthens the progression of vascular sclerosis; therefore, pulse pressure has a certain role in reflecting the degree of arteriosclerosis [ 13 ]. As obtained from this experiment, according to the AASI grouping, as the AASI level increases, 24 h PP is gradually increasing, but the stability of PP is weaker than that of AASI and is susceptible to changes in blood pressure fluctuations and other factors and affects the accuracy of prediction, so the AASI in this study has become the most suitable indicator for predicting arteriosclerosis [ 14 ].…”
Section: Results and Analysismentioning
confidence: 99%
“…If the axial rotation range of the chest and hip joint is reduced, the pressure on the lumbar muscles and joints will increase, thus increasing the risk of lumbar injury. Therefore, it is necessary to increase the stretching activity of chest muscles in daily training to fully relax the chest in a state of tension for a long time [ 27 ].…”
Section: Results and Analysismentioning
confidence: 99%
“…The experiment shows that the main reason for the error rate is the delay of the inspection results of financial abnormalities [23]. Through the example analysis, it can be concluded that the proposed intelligent analysis method of financial abnormal data based on deep learning has good effectiveness and accuracy and has certain practical value [24].…”
Section: Results Analysismentioning
confidence: 99%